KARAKTERISTIK HAMBA TUHAN BERDASARKAN 2 TIMOTIUS 2:22-25 - David Susilo Pranoto (Manna Rafflesia, 2016)
In this paper the author discusses "Characteristics of God's servants" based on 2 Timothy 2: 22-25. Characteristics are characteristics possessed by someone who distinguishes himself from others in which discuss about character and which leads to good moral values ​​(ethical). This characteristic is also a characteristic that is embedded in the servants of God in their lives interacting with others, to themselves, the surrounding environment and in the ministry. The Apostle Paul in his letter to Timothy so that Timothy as a servant of God does not fall into sin in the face of various temptations of faith that lead to sin, trials, false doctrines, false teachers and various other challenges both inside and outside. Therefore the Apostle Paul advised Timothy to maintain holiness by having the characteristics of God's servants.